Analysis of end crack in boiler tube - Begum, Shahida; Karim, A.N. Mustafizul; Nainer, Mohamed Ansari M.; Sevah, Sukhana (Trans Tech Publications Ltd., Switzerland, 2012)
Boiler tube failures usually result in frequent forced outages, and ultimately in costly extended outages for major tubing replacement in a plant. There are several failure modes that may occur in a boiler tube, i.e. stress-corrosion cracking, pitting, water-side corrosion, fire-side corrosion, fatigue failure, overheating, dissimilar metal weld fatigue, mechanical fatigue and erosion. In this research the failure modes of boiler and its end cracks due to the dissimilar metal weld is analyzed. Hence data are collected and explored to determine the cause of failure and as a solution ceramic ferrule is suggested. The use of ceramic ferrule in boiler tube can eliminate the crack occurrence or delay the process due to thermal properties. The prevention of crack will reduce frequent maintenance and thus the cost of operation can be minimized.